Impactul pandemiei asupra statului de drept și libertăților fundamentale ale omului. [Articol] - Chirtoacă, Lilia (CEP USM, 2021)
Finding a balance between fundamental liberties, on the one hand, and the public health policies required for overcoming the crisis wrought by the pandemic, on the other hand, is a difficult task. In this context, it is essential to evaluate the necessity and proportionality of the legislation adopted in the period of public health emergency, as well as identify efficient guarantees in the case where governments put in place exceptions, derogations, or restrictions on human rights. More specifically, these limitations on human rights need to be examined according to the tests of legality, legitimacy, and proportionality.
THE IMPACT OF THE PANDEMIC ON THE RULE OF LAW AND THE FUNDAMENTAL LIBERTIES OF HUMAN BEINGS
Keywords: derogation in time of emergency; rights and freedoms; the ECHR jurisprudence; international standards; derogation to human rights; emergency measures; global health crisis; exceptional situations; proportionality; temporariness; necessity